2009
DOI: 10.1002/btpr.188
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence enhancement of warfarin induced by interaction with β‐cyclodextrin

Abstract: Warfarin is the most common agent used for control and prevention of venous as well as arterial thromboembolism (blood clots). In aqueous media, warfarin forms inclusion complexes with a family of cyclic oligosaccharides, alpha, beta, gamma-cyclodextrins (CD). The formation of these complexes results in enhancement of the fluorescence of warfarin. Such spectroscopic changes offer a venue for the development of bioanalytical methodologies for warfarin quantification in biological liquids. We characterized the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 37 publications
7
36
0
Order By: Relevance
“…5). This finding indicated that an increase in the ThT emission The observed emission enhancement phenomenon, induced by the endospore uptake, is consistent with the sensitivity of the photophysical properties of ThT to the viscosity of the environment: i.e., the emission quantum yield of ThT increases with the increase in the medium viscosity (72,74,81,82,88,90). Due to the single carbon-carbon bond between the two ring systems and the single carbon-nitrogen bond between the phenyl ring and the dimethyl amine (Fig.…”
Section: Resultssupporting
confidence: 77%
“…5). This finding indicated that an increase in the ThT emission The observed emission enhancement phenomenon, induced by the endospore uptake, is consistent with the sensitivity of the photophysical properties of ThT to the viscosity of the environment: i.e., the emission quantum yield of ThT increases with the increase in the medium viscosity (72,74,81,82,88,90). Due to the single carbon-carbon bond between the two ring systems and the single carbon-nitrogen bond between the phenyl ring and the dimethyl amine (Fig.…”
Section: Resultssupporting
confidence: 77%
“…4b), the ratios between which are concentration dependent. We ascribe the red-shifted peak, the intensity of which increases with an increase in concentration, to aggregates that form at the excited and/ or the ground state [46,[75][76][77][78][79][80]. The trends from this assignment of the fluorescence spectra indicate that the chlorinated hydrocarbons, such as DCM, tend to suppress aggregation (Fig.…”
Section: Photophysical Propertiesmentioning
confidence: 85%
“…A typical instrumental pulse using an IBH TBX-04 detector at a time calibration of 13 ps per channel and a scattering sample of LUDOX 1 was about 600 ps at full width half maximum. To remove the additional excitation pulse Ishiwata and Kamiya (1997), Vasquez et al (2009) from the NanoLed at around 430 nm, a cut-off filter (UG-11) was kept in front of the excitation source. Before every sample measurement, the instrument response function was measured using LUDOX 1 solution (excitation and emission wavelengths 295 and 334 nm respectively).…”
Section: Time-resolvedmentioning
confidence: 99%